Kepemimpinan Islami dalam Mengantisipasi Perubahan Pendidikan ke Era Digital - Zahro, Ula Masrurotuz Z (Education Management: Jurnal Manajemen Pendidikan Islam, 2024)
The study emphasizes the importance of Islamic values-based leadership in navigating challenges and leveraging the potential of digital technology effectively. The aim is to analyze how Islamic leadership principles can be applied in digital education to create an inclusive, equitable, and pride-enhancing learning environment. A descriptive qualitative approach with a case study focus was employed, allowing in-depth analysis of Islamic values based leadership practices in digital educational institutions. Findings indicate that leaders grounded in Islamic values effectively lead with integrity, facilitate collaboration, and integrate technology to enhance educational quality.